UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEGIATAN EKONOMI DI SEKOLAH DASAR - Hasibuan, Sulhan Efendi; Harahap, Asriana; Harahap, Maisah Fitri (DIRASATUL IBTIDAIYAH, 2022)
Abstract The background of this research problem is the low student learning outcomes in learning Social Sciences (IPS) in the classroom. The formulation of the problem in this research is whether through the Snowball Throwing learning model can improve student learning outcomes in Social Sciences (IPS) subjects on economic activity in class V in SDN 200508 Sihitang. While the research objective is to determine the extent to which the application of the Snowball Throwing learning model can improve learning outcomes in Social Sciences (IPS) class V SDN 200508 Sihitang. The type of research used is Classroom Action Research using two cycles, and each cycle of 2 meetings. One cycle consists of planning (planning), action (action), observation (observasing), and reflection (reflection). Based on the results of the research conducted, it can be concluded that the Snowball Throwing learning model can improve student learning outcomes in the material of economic activities in Indonesia in class VA SDN 200508 Sihitang. From the second cycle the data obtained has reached the expected value with the highest percentage, namely 81.48%, so this research can be stopped with a satisfactory value. Keywords: Learning Outcomes, Students, Economic Activities.